Validation of the menstrual sensitivity index in adolescents - Laura C. Seidman; Ariel B. Handy; Laura A. Payne (PAIN Reports)
Abstract. Introduction:. The Menstrual Sensitivity Index (MSI), assessing the attunement to and fear of menstrual symptoms, was recently developed and validated in an adult sample. Objectives:. The objective of this study was to validate the MSI in adolescents. Methods:. One hundred forty-one girls aged 13 to 19 participated in a larger parent study on primary dysmenorrhea, and their data were used in the present study. Girls participated at 2 timepoints: baseline (N = 141) and a 1-year follow-up (N = 115). At each timepoint, participants completed the MSI and a variety of self-report measures. Results:. A confirmatory factor analysis supports the previously identified factors of the MSI (somatic anxiety, fear/danger, and medication) in adolescent girls. The MSI demonstrates good item-total correlations, internal consistency, and test–retest reliability. The MSI converged most strongly with pain catastrophizing and diverged most strongly from body pain. Conclusion:. The MSI is a valid and reliable measure of attunement to and fear of menstrual symptoms in adolescents. Unlike research in adult women demonstrating convergence between the MSI and menstrual pain and menstrual symptom severity, the divergence between the MSI and these variables in the current study suggests that, for adolescents, menstrual sensitivity is more strongly related to fear of pain than menstrual pain itself. These findings provide considerations for future research and clinical practice addressing menstrual pain and symptoms in adolescents.